2021
DOI: 10.1007/978-3-030-84252-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Outside the Superbox

Abstract: Designing a block cipher or cryptographic permutation can be approached in many different ways. One such approach, popularized by AES, consists in grouping the bits along the S-box boundaries, e.g., in bytes, and in consistently processing them in these groups. This aligned approach leads to hierarchical structures like superboxes that make it possible to reason about the differential and linear propagation properties using combinatorial arguments. In contrast, an unaligned approach avoids any such grouping in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This alteration extends the length of the final block, consequently influencing the modular multiplication and modular exponentiation phases when dealing with the larger block size. Furthermore, replacing SHA256 with another cryptographic hash function (CRH) like SHA3 [58] or Keccak [59] has implications for both schemes. In Khadr's scheme, this substitution will make the size of the final block larger ( > 3327 bits).…”
Section: Phasementioning
confidence: 99%
“…This alteration extends the length of the final block, consequently influencing the modular multiplication and modular exponentiation phases when dealing with the larger block size. Furthermore, replacing SHA256 with another cryptographic hash function (CRH) like SHA3 [58] or Keccak [59] has implications for both schemes. In Khadr's scheme, this substitution will make the size of the final block larger ( > 3327 bits).…”
Section: Phasementioning
confidence: 99%
“…When bits cluster in columns it results in a state having a column branch number under λ smaller than the bit branch number under θ. The effect of active bits at the output of θ ending up in the same column after λ is called bit huddling [8]. In this phase, for all R w values we check whether for the 11 states with bit branch number 12 there is bit huddling at the output of λ and keep only those where there is none.…”
Section: Selecting the Offsets Of R Wmentioning
confidence: 99%
“…A study in [8] provides evidence that this approach outperforms MDS-based designs in that they achieve lower upper bounds on the probability of differential trails and the correlation contribution of linear trails for the same amount of computation, often due to lighter rounds. Moreover, the paper shows that they suffer less from clustering of trails.…”
Section: Introductionmentioning
confidence: 99%
“…The list has 201 entries. In [8] it is reported that all 3-round trails with weight up to 50 are lone Markov trails. The lowest weight, 36, is attained by 4 trail core classes, hence under reasonable assumptions, we have MDP f = 2 −36 .…”
Section: Mdp F and Mndp F Of Xoodoo[3]mentioning
confidence: 99%
“…Clearly, as the weight of trails increases, the likelihood of clustering and dependence of round differentials does increase. Still, as discussed in [8], it is unlikely these effects are noticeable for trails with relatively low weight in permutations with round functions in which no superboxes can be identified. Xoodoo is such a permutation and any trails leading to the best collision attacks would have weight well below the permutation width that is 384.…”
Section: Mdp F and Mndp F Of Xoodoo[3]mentioning
confidence: 99%